2012
DOI: 10.4028/www.scientific.net/amr.557-559.2361
|View full text |Cite
|
Sign up to set email alerts
|

Design and Simulation of Ascending Curvilinear Micro Channel for Cancer Cell Separation from Blood

Abstract: Cancer is one of the leading causes for human death. However, if cancer cells are identified at initial stage, patient treatment will be low cost and successful. This research presents the design and simulation of ascending curvilinear micro channel for separation of particles resembling cancer cells. The separation system is designed and simulated by using inertia focusing cell separation technique. Computational fluid dynamics (CFD) design and simulation of ascending micro channel for cell separation using i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Most often, malignant cells are separated via these microchannels. In order to separate malignant cells from blood, Wewala et al (2012) examined the shape and simulation procedure of ascending curvilinear channel. They separated cells using the inertia-focusing method.…”
Section: Curvilinear Microchannelmentioning
confidence: 99%
See 2 more Smart Citations
“…Most often, malignant cells are separated via these microchannels. In order to separate malignant cells from blood, Wewala et al (2012) examined the shape and simulation procedure of ascending curvilinear channel. They separated cells using the inertia-focusing method.…”
Section: Curvilinear Microchannelmentioning
confidence: 99%
“…100 x 10 -6 m was the bare minimum inner radius. The channel had a length of 14450 x 10 -6 m and a maximum inner radius of 1150 x 10 -6 m. Only one input and three outlets were needed for the two ascending and descending microchannels to cooperate 153) . A unique design of ascending and descending curvilinear microchannels was reported by Wewala et al (2013).…”
Section: Curvilinear Microchannelmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently microfluidic devices have been explored for the seperation of cancer cells from model mixtures and patient blood [13][14]. Bhagat et al (in 2008) successfully demonstrated particle separation in spiral microchannels using dean flows based on CFD modeling; they investigated that separation process based on the particle size [15]. Density variation between two fluids can create asymmetric pair of dean vortices as the fluids pass through the curve.…”
Section: Introductionmentioning
confidence: 99%
“…Carlo presented a rapid micro fluidic filtration technology for separating particles with purities from 90 to 100% and high-volume throughputs of 1 ml/min [23]. In 2008, Bhagat et al presented a passive microfluidic device of 5-loop spiral microchannel geometry [15]. Lee et al reported a contraction-expansion array (CEA) microchannel which execute inertial size separation through a force balance between dean drag and inertial lift forces.…”
Section: Introductionmentioning
confidence: 99%